Hubungan Pengetahuan Ibu Dengan Penanganan Demam Pada Anak Usia 1-5 Tahun Diwilayah Kerja Puskesmas Bohabak - Anggelia Van Gobel; Kristine Dareda; Rahmat Hidayat Djalil (STIKES Columbia Asia Medan, 2023)
Febris or fever is a state when the body temperature becoming higher than usual, and this is a symptom of illness. Body temperature that is said to be normal ranges from 36.5-37.50C. This study aims to determine the relationship between maternal knowledge and fever management in children aged 1-5 years in the working area of the Bohabak health center. This study used a correlation analytical method with a cross sectional design. The sample was taken based on the number of subject as many as 30 people using purposive sampling. Data collection was carried out by means of interviews and filling out questionnaires. Furthermore, the data collected processed using the SPSS Version 16.0 of computer program to be analyzed using the Chi-Square test with a meaning level (α) of 0.05. The results showed there were subjecet with the knowledge and fever management well as much as 5 (16.7%), and good maternal knowledge with poor fever management as much as 0 (0.0%). While the mother's knowledge is not good with good fever management as much as 4 (13.3%) and maternal resistance is not good with poor fever management as much as 21 (70.0%). In the ρ Value 0.000 This value ρ is smaller than the value α=0.005. The conclusion : there were the relationship between maternal knowledge and fever management in children aged 1-5 years in the Bohabak Health Center area. The suggestion of this study is to increase the knowledge of mothers in handling fever.